2014
DOI: 10.1007/s13197-014-1392-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties and structure changes of soybean protein isolate after subcritical water treatment

Abstract: Subcritical water is an emerging method in food industry. In this study, soybean protein isolate (SPI) was treated by subcritical water (SBW) at various temperatures (0, 120, 160, 200°C) for 20 min. The changes in the appearances, physicochemical properties and structural changes were investigated. After SBW treatment, the color of SPI solution modified turned to be yellow. The mean particle size and turbidity of SPI had similar behaviors. The mean particle size was decreased from 263.7 nm to 116.8 nm at 120°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…Fourier transform infrared (FTIR) spectroscopy was carried out on solid samples by KBr pelleting method using Perkin Elmer Spectrum-100 model (Zhang et al 2015). Secondary structure quantitations were performed by the Gaussian curve-fitting of the spectrum in the Amide I region (Shevkani et al 2015).…”
Section: Surface Hydrophobicity μGmentioning
confidence: 99%
“…Fourier transform infrared (FTIR) spectroscopy was carried out on solid samples by KBr pelleting method using Perkin Elmer Spectrum-100 model (Zhang et al 2015). Secondary structure quantitations were performed by the Gaussian curve-fitting of the spectrum in the Amide I region (Shevkani et al 2015).…”
Section: Surface Hydrophobicity μGmentioning
confidence: 99%
“…[18] Remarkable improvement of emulsifying ability and physical stability of emulsion by subcritical water treatment was probably associated with higher surface protein loads. [19] Subcritical water treatment could significantly enhance the emulsifying and foaming properties and solubility of SPI and could modify the structure of SPI, [20] which demonstrated that the subcritical water pretreatment could change the structure and improve the functional properties of SPI.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the most critical functional properties, water solubility is a vital characteristic of a protein in the acceptability of beverages, additives and fortifier (Ito et al ., ; Zhao et al ., ; Zhang et al ., ). The solubility of WSMP, SPI and WPI is illustrated in Fig.…”
Section: Resultsmentioning
confidence: 97%
“…These results suggested that solubility might not be the only factor determining protein adsorption at the oil‐/water interface. It had been indicated that surface hydrophobicity of a protein was a critical factor in affecting the emulsifying properties (Wang et al ., ; Ghribi et al ., ; Zhang et al ., ). The increased hydrophobic groups exposed on protein surface would promote the interaction between the protein and lipid phase (Fig.…”
Section: Resultsmentioning
confidence: 97%